Third Trimester Myocardial Performance Index in Fetuses from Women with Hyperglycemia in Pregnancy: A Systematic Review and Meta-Analysis - Sirico, Angelo; Raffone, Antonio; Maruotti, Giuseppe Maria; Travaglino, Antonio; Paciullo, Carmela; Diterlizzi, Alice; Mollo, Antonio; Rizzo, Giuseppe; Zullo, Fulvio; Lanzone, Antonio (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
Introduction The myocardial performance index (MPI) has been proposed to evaluate cardiac dysfunction in newborns from diabetic mothers. Although MPI is routinely assessed in newborns, its role in the evaluation of fetuses from women with hyperglycemia in pregnancy (HIP) is still under evaluation. We aimed to evaluate the differences in third trimester fetal MPI in pregnant women with hyperglycemia compared to healthy controls.Materials and Methods Seven electronic databases were searched for all studies assessing women with HIP who underwent evaluation of fetal left MPI during pregnancy compared to a control group. The summary measures were reported as mean differences (MD) in the mean fetal left MPI between women with HIP and healthy controls, with a 95 % confidence interval (CI). A post hoc subgroup analysis based on the type of HIP – pregestational diabetes, GDM, or gestational impaired glucose tolerance (GIGT) – was performed as an additional analysis.Results 14 studies assessing 1326 fetuses (580 from women with HIP and 746 from controls) were included. Women with HIP had a significantly higher mean left fetal MPI compared to controls (MD 0.08; 95 %CI: 0.05 to 0.11; p < 0.00 001). Subgroup analysis according to the type of HIP concurred with the overall analysis for women with DM (MD 0.07; 95 %CI: 0.01 to 0.13; p = 0.02) and for women with GDM (MD 0.012; 95 %CI: 0.07 to 0.17; p < 0.00 001) but not for women with GIGT (MD –0.01, 95 % CI –0.28 to 0.27; p = 0.96).Conclusion Fetal left MPI is increased in pregnancies with HIP appearing as a potential marker of cardiac dysfunction.
Keywords: hyperglycemia; pregnancy; fetal ultrasound; fetus; echocardiography